La memoria risorgimentale in Giustizia e Libertà (1929-1940) - Pernicone, Agata <1978> (Alma Mater Studiorum - Università di Bologna, 2009)

(untitled)
The dissertation regards The memory on the Italian Risorgimento in “Justice and Freedom”(1929-1940) a theoretical core point in the history of the Movement, which so far has not been granted due attention. The work herewith presented is therefore aimed at filling a storiographical gap, analysing the historical events which continue to operate as traditions, raising feelings and passions and hence operating in politics, although as secondary factors. The point made is that the Justice and Freedom Movement, an antifascist political movement born in Paris in October 1929, bases its strength on the heroic choice of the antifascism movement to fight a Second Risorgimento, connecting the fight against the regime to the battles previously fought for the justice and the freedom, an entirely isolated event in the political opposition’s panorama. The dissertation, thus, attempts to explain how and why Justice and Freedom is so tightly interconnected in its political action to the Risorgimento tradition. The first chapter sets the cultural background of the foundation of the Justice and Freedom Movement. The centre of such foundation was Florence, where Gaetano Salvemini, along with a group of young people, would later on carry out some cultural experiences that ideally prepare the ground for the movement’s birth. In the second chapter are found the sites of the memory where the passage of the Risorgimento tradition between the generations takes place. The work therefore shifts from a public to a private level, concentrating on biographical paths. The choice made was for Nello Rosselli, a man very close to the Justice and Freedom Movement but who, as opposed to his comrades-in-arms, did not chose the political way to express his ethical choice, but rather the theoretical one, becoming a Risorgimento historian. The third chapter concentrates on the birth of the Justice and Freedom Movement in France, trying to reconstruct the cultural ties and the confrontation places and sites where the members of the Movement could interact with the French intellectual milieu, bringing back to light the propagandistic usage of the Risorgimento myth carried out by the Movement. Lastly, the fourth chapter focuses on the cultural debate on the Risorgimento, which took place on the press organs of the Movement, pointing out and periodizing the theoretical passages and the propagandistic uses of the myth as related to the stages of the Movement and the political needs.